2021
DOI: 10.15584/ejcem.2021.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in haematological parameters and serum beta-2-microglobulin levels in CD4+ T-cells-stratified Nigerian HIV patients

Abstract: Introduction. Reports have shown that there is a rise in beta-2-microglobulin (β2M) concentration in patients with HIV infection and that the degree of elevation correlates well with the extent of disease burden and could be an independent prognostic marker for death. However, there is the dearth of information on the interplay between alteration in haematological profile, a common cause of morbidity and mortality in HIV, and β2M. Aim. Changes in selected haematological parameters and β2M in Nigerian HIV patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is noted that haematological profiles tend to be exceptionally quick, basic and economical tools, especially in resource-limited countries such as sub-Saharan Africa. Epidemiological studies revealed that HIV infection is associated with gradual damage to the body’s immune and haematological systems which results in alteration of the haematological parameters,8–11 changes in these parameters have been suggested as alternative markers of the severity and prognosis of the disease. A study found 72%, 18%, 49% and 15% prevalence of anaemia, leucopenia, lymphopenia and thrombocytopaenia among HIV-infected patients, respectively 12.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that haematological profiles tend to be exceptionally quick, basic and economical tools, especially in resource-limited countries such as sub-Saharan Africa. Epidemiological studies revealed that HIV infection is associated with gradual damage to the body’s immune and haematological systems which results in alteration of the haematological parameters,8–11 changes in these parameters have been suggested as alternative markers of the severity and prognosis of the disease. A study found 72%, 18%, 49% and 15% prevalence of anaemia, leucopenia, lymphopenia and thrombocytopaenia among HIV-infected patients, respectively 12.…”
Section: Introductionmentioning
confidence: 99%